Subject’s constitutional reactivitya. Interdisciplinary “rosetta stone” - Magliozzi, Pietro (Acta Bioethica, 2014)
To learn to identify in an integral, mixed and dynamic way the subject’s constitution means, on one hand, to help him to a self-knowledgement of his reactive way (for this, we speak of constitutional reactivity and no more of biotipe or trait), to develop himself (to mature or to destroy), to join and accept the others like they are; on the other way, it serve to personalize diagnosis, therapy and prognosis. The constitution history and a synoptic interdisciplinary diagram (Greek philosophy, theology, hippocratic, galenic, homeopatic, chinese, ayurvedic and holistic medicines, biology, embriology, biochemistry, physiopathology, neurology, endocrinology, psychology and spirituality) shows a precise link and a common denominator according to an embriologic constitutional theory, that speaks about endoblast, mesoblast and ectoblast. A coherence thas lasts for more than 24 centuries in occident and goes through even the cultural borders (eastern and western world) and paradigmatic logics (biomedicine and homeopaty) cannot be casual.